Faunal knowledge of students in rural schools: a guide for their recognition in science class - Hernández-Barbosa, Rubinsten (2018)
This text aims to describe a methodological proposal to identify, classify, and organize the faunistic knowledge of students of rural schools. The research was conducted with twenty sixth graders from a rural school in the Department of Cundinamarca, Colombia. Through five types of activities, they expressed, in different ways, their knowledge about the animals of the region. The information collected was organized, categorized, and systematized in tables; these tables resulted from the analysis of the information the students provided. It is a possibility of school work that favors the recognition and valuation of the traditional and ancestral knowledge, and its incorporation to the dynamics of the teaching and learning of the Natural Sciences as a way to create “bridges” between that knowledge and the scholarly scientific knowledge. It is a proposal that, among other things, favors the development of more positive attitudes toward science itself, motivates students to ask questions, to recognize the importance of the cultural context, and to recognize themselves as part of a biocultural system.